Investor’s Perception: Sustainable Development Through Investment Avenues in India - Nabeel. K, Mohammed; Sumathy, M. (NIDA Development Journal, 2023)
The purpose of this study is to examine investors' attitudes on long-term investments in India. Using the snowball sampling technique, a questionnaire-based poll was undertaken to collect responses from 216 cryptocurrency investors. According to the study, investors' perceptions of risk and return on sustainable investments are influenced by demographic parameters such as age, educational qualification, and investment experience. It was also shown that the most important reason for investing in sustainable investments is the security of the investment and that energy conservation is an important criterion to consider before investing. According to the findings of this study, investors should place a greater emphasis on the importance of integrating sustainable development into the transition to a more responsible and sustainable financial system.